ANALYSIS OF THE INFLUENCE OF WORK MOTIVATION, COMPETENCE, AND COMPENSATION ON THE EFFECTIVENESS OF THE MANAGEMENT OF VOTING AND VOTE COUNTING BY KPPS IN THE 2024 LEGISLATIVE ELECTION IN PARIAMAN CITY - Junaidi, Dedy; Frinaldi, Aldri (Universitas Padjadjaran, 2025)
This study aims to analyze the influence of work motivation, competence, and Compensation on the effectiveness of vote collection and counting management by the Voting Organizing Group (KPPS) during the 2024 Legislative Election in Pariaman City. The effectiveness of election management at the polling station (PST) level is a crucial factor in ensuring the integrity, accountability, and transparency of the democratic process. This research uses a quantitative approach with an associative research design. The sample consists of 334 respondents selected from a population of 2,023 KPPS members using the Taro Yamane formula. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with the help of SPSS version 26. The results indicate that the three independent variables—work motivation, competence, and Compensation—have a positive and significant impact on the effectiveness of vote collection and counting management, both individually and in combination. Work motivation plays a crucial role in encouraging enthusiasm, responsibility, and integrity among KPPS members. Competence ensures that tasks are carried out professionally and in accordance with procedures, while fair Compensation increases job satisfaction and loyalty. Simultaneously, these three factors form a synergy that determines the success of election administration at the grassroots level. These findings underscore the importance of comprehensive human resource management for the Pariaman City General Elections Commission (KPU), particularly in enhancing motivation, strengthening competence, and implementing a proportional compensation system. Thus, the quality of election governance can be improved toward effective, transparent, and integrity-based election implementation.